REPRESENTATION OF YOUTH IN LOCAL ASSEMBLIES IN SERBIA - Stojanović, Boban (Serbian political thought, 2024)
This paper examines the representation of young people in local assemblies and the variables that may influence it. The first part of the paper deals with the legal status of youth in the Serbian legal system, youth participation, local government, and local elections, as well as the instruments of local youth policy. We then present the methodological approach and the methods used for data collection, coding in SPSS, and the creation of dependent and independent variables. The first set of variables relates to the demographic characteristics of municipalities and cities, the second set pertains to scholarships for pupils and students, and the third set concerns youth local policies aimed at improving youth participation in decision-making processes. The total number of young councilors in Serbia is 386 out of 6,483 councilors, representing 5.95%. Through correlation analysis, we rejected all hypotheses except that the type of local government, the number of voters and councilors, and the size of the municipality or city have the greatest influence on the number of young councilors, although with a weak or moderate correlation. We rejected all hypotheses regarding the influence of student and pupil scholarships and local youth policy instruments on the number and percentage of young councilors in local government units. We have determined that support for pupils and students, as well as the instruments of local youth policy, do not influence the increase in the number of young councilors in the assemblies of local government units in Serbia.
Keywords: youth; councilors; political representation; youth participation; local youth policy